Modelling accessibility for public transport in an urban context - Kalsaas, Bo Terje; Aase, Eivind (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
The aim of the paper is to analyse modelling of accessibility for public transport in an urban context. A network Geographical Information System (GIS) application (TransCAD) is applied for this purpose. In comprehensive transport and land use planning, access to different sites from the resi-dential areas of an urban region is of great interest. Calculating accessibility measured in travel time is a relatively easy task for transport by car, bicycling and walking, but it is much more challenging for public transport. That stems from the rigidity of such systems related to infrastructure, and the fact that passengers on a trip may have to change line and might have several routes to select from. The paper discusses methods for calculation of accessibility on three levels of detail: 1) from terminal to terminal; 2) from a geographical zone to another zone; and 3) from address to address. While the first two levels are tested in a study, the third and most challenging one is limited to a conceptual discussion.